Insights into modular polyketide synthase loops aided by repetitive sequences. Issue 9 (28th April 2021) - Hirsch, Melissa; Kumru, Kaan; Desai, Ronak R.; Fitzgerald, Brendan J.; Miyazawa, Takeshi; Ray, Katherine A.; Saif, Nisha; Spears, Samantha; Keatinge‐Clay, Adrian T.
Abstract: The loops of modular polyketide synthases (PKSs) serve diverse functions but are largely uncharacterized. They frequently contain amino acid repeats resulting from genetic events such as slipped‐strand mispairing. Determining the tolerance of loops to amino acid changes would aid in understanding and engineering these multidomain molecule factories. Here, tandem repeats in the DNA encoding 949 modules within 129 cis ‐acyltransferase PKSs were cataloged, and the locations of the corresponding amino acids within the module were identified. The most frequently inserted interdomain loop corresponds with the updated module boundary immediately downstream of the ketosynthase (KS), while the loops bordering the dehydratase are nearly intolerant to such insertions. From the 949 modules, no repetitive sequence loop insertions are located within ACP, and only 2 reside within KS, indicating the sensitivity of these domains to alteration.